An Analysis Type of Idioms Expression Used by Character Found in Movie Bohemian Rhapsody - Mite, Ino; I Putu Andri Permana (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
This analysis aimed to identify the multiple idiomatic statements that were detected in the movie Bohemian Rhapsody. O'Dell and McCarthy's theory was employed in this investigation (2010). The data source study gathered the data by browsing and downloading movies and the script from the internet, reading and figuring out the movie, taking notes, and classifying. This study adopted qualitative research as its technique. This research methodology uses qualitative research. collect data by watching films and reading film scripts. After the data is collected, this research prepares the data, then performs calculations as data analysis. After looking for idiomatic expressions in the film while re-reading the script, this research found 14 idiomatic expressions. O'Dell and McCarthy's theory suggests (2010), Idioms are divided into six different categories; Binomials, proverbs, euphemisms, fixed statements, and other languages, as well as similes. The results of data analysis show that of the 14 types of patented expressions, the types of phrases innovated in this movie are: simile( 2), binomial( 1), proverb( 2), euphemism( 2), cliche( 2), fixed statement( 5). This study concludes that in the film Bohemian Rhapsody, the most dominant patented expression used is a fixed statement with an aggregate of 5 data points.